TINJAUAN UMUM TENTANG PERTANGGUNGJAWABAN KEJAHATAN DAN PIJAKAN KRIMINAL ANAK - Reny Okprianti; Nur Husni Emilson; Fadiah Adilah Kusmayadi; Grevina Tasya Abellia; Holidiansyah Marsya Ika; Artanti Mayasari (LPPM STIH Awang Long, 2025)
As time goes by, the challenges in raising and nurturing children are becoming increasingly complex. Cases of juvenile delinquency leading to dangerous behavior are becoming more frequent, such as student brawls, drug abuse, bullying, and promiscuity that can lead to pregnancy and abortion. This study employs a normative approach. The context of children in conflict with the law is crucial for distinguishing criminal liability for children from that for adults. This is because while all actions by adults constitute crimes, they constitute delinquency for children. This study identified challenges in the implementation of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (UU SPPA), such as a lack of understanding among law enforcement officials about the concept of restorative justice and a lack of rehabilitation facilities in the regions. The results of this study emphasize the important role of families, schools, and communities in preventing criminal acts by children and the need to optimize diversification and rehabilitation policies.